Skilled migration: the perspective of developing countries - Frederic Docquier; Hillel Rapoport (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
This chapter focuses on the effects of skilled migration on developing countries. We first present new evidence on the magnitude of the "brain drain" at the international level. Using a stylized model of education investment in a context of migration, we then survey the theoretical and empirical brain drain literature in a unified framework. Finally we use a particular specification of the model to discuss a number of policy issues from the perspective of developing countries.
Keywords: 330; Migration; Brain Drain